EXPOSE SYNOPTIQUE DES DONNEES ECOBIOLOGIQUES SUR LE MEROU BRUN EPINEPHELUS MARGINATUS(SERRANIDAE) DES COTES DE L’EST ALGERIEN (Sciences & Technologie. C, Biotechnologies, 2007)
A study of biology, ecology and genetics of the dusky grouper, Epinephelus marginatus(LOWE, 1834) were carried out in the gulf of Annaba (north-eastern of Algeria). It brings new information on the morphology of this species, its growth, its habitat, its behaviour in the natural environment, its mortalities (natural and by fishing), its diet from summer, its intraspecific sexuality and its phylogenic relations. A bibliographical compilation on the subject is presented by trying a comparison with our results.